Catholic Mobilizations in Twentieth-Century Mexico: From Pious Lynchings and Fascist Salutes to a "Catholic 1968, " Maoist Priests, and the Post-Cristero Apocalypse. Issue 2 (April 2022) - Butler, Matthew
Abstract : This special issue, fruit of an American Historical Association panel on the entanglements of Catholicism and nationhood after Mexico's Cristero War (1926-29), offers five new histories that cumulatively give the lie to anything so monolithic as a twentieth-century "Catholic history." As is well known, the Cristero War was a major armed confrontation between the Church and the postrevolutionary state and their respective bases, followed, as the story goes, by an uneasy truce and an enduring coexistence lasting for decades, to the 1950s and perhaps to the 1970s.